Pengaruh Brand Awareness Terhadap Minat Beli Produk Terafiliasi Israel Di Kalangan Mahasiswa FDK UIN SU - Nur Azmi Fauzizah; Tengku Walisyah (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
Israel's aggression against Palestine has claimed many lives, damaged important infrastructure such as schools, hospitals, and private assets. Indonesia rejects Israeli aggression against Palestine by boycotting Israeli-affiliated products as MUI fatwa No. 83 of 2023 concerning support for the Palestinian cause. This study aims to examine whether there is an effect of brand awareness on purchase intention of Israeli-affiliated products among FDK UIN SU students. This research uses a quantitative approach with non-probability sampling technique, namely purposive sampling. The sample size was 100 students determined through the Slovin formula with a margin of error of 10%. Data collection instruments through questionnaires using a Likert scale. The SPSS version 26 application was used to statistically analyze the data. The results showed that brand awareness affects the purchase intention of Israel-affiliated products among FDK UIN SU students by 14.2%, while 85.8% is influenced by other variables not explained in this study. The direction of the effect is negative, meaning that the higher the brand awareness, the lower the purchase intention. This shows that high brand awareness decreases purchase intention which indicates that students boycott Israeli-affiliated products.